CAR T cells targeting the ganglioside NGcGM3 control ovarian tumors in the absence of toxicity against healthy tissues - Cribioli, Elisabetta; Giordano Attianese, Greta Maria Paola; Coukos, George; Irving, Melita (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR) T cells have emerged as a powerful immunotherapeutic tool against certain hematological malignancies but a significant proportion of patients either do not respond or they relapse, sometimes as a result of target antigen loss. Moreover, limited clinical benefit has been reported for CAR therapy against epithelial derived solid tumors. A major reason for this is the paucity of solid tumor antigens identified to date that are broadly, homogeneously and stably expressed but not found on healthy tissues. To address this, here we describe the development and evaluation of CAR T cells directed against N-glycoslylated ganglioside monosialic 3 (NGcGM3). NGcGM3 derives from the enzymatic hydroxylation of N-acetylneuraminic acid (NAc) GM3 (NAcGM3) and it is present on the surface of a range of cancers including ovarian, breast, melanoma and lymphoma. However, while NAcGM3 is found on healthy human cells, NGcGM3 is not due to the deletion of an exon in the gene encoding for the enzyme cytidine monophospho-N-acetyl-neuraminic acid hydroxylase (CMAH). Indeed, unlike for most mammals, in humans NGcGM3 is considered a neoantigen as its presence on tumors is the result of metabolic incorporation from dietary sources. Here, we have generated 3 CARs comprising different single chain variable fragments (scFvs) originating from the well-characterized monoclonal antibody (mAb) 14F7. We show reactivity of the CAR T cells against a range of patient tumor fragments and we demonstrate control of NGcGM3+ SKOV3 ovarian tumors in the absence of toxicity despite the expression of CMAH and presence of NGcGM3+ on healthy tissues in NSG mice. Taken together, our data indicate clinical potential for 14F7-based CAR T cells against a range of cancers, both in terms of efficacy and of patient safety.